One‐year follow‐up on liraglutide treatment for prediabetes and overweight/obesity in clozapine‐ or olanzapine‐treated patients. (28th November 2018) - Svensson, C. K.; Larsen, J. R.; Vedtofte, L.; Jakobsen, M. S. L.; Jespersen, H. R.; Jakobsen, M. I.; Koyuncu, K.; Schjerning, O.; Nielsen, J.; Ekstrøm, C. T.; Correll, C. U.; Vilsbøll, T.; et al.
Abstract : Objective: Treatment with most antipsychotics is associated with an increased risk of weight gain and metabolic disturbances. In a randomized trial, we previously demonstrated that 16 weeks of glucagon‐like peptide‐1 receptor agonist liraglutide treatment vs. placebo significantly reduced glucometabolic disturbances and body weight in prediabetic, overweight/obese schizophrenia‐spectrum disorder patients treated with clozapine or olanzapine. The aim of this study was to investigate whether the beneficial effects of the 16‐week intervention were sustained beyond the intervention period. Method: One year after completion of the intervention, we investigated changes in body weight, fasting glucose, glycated hemoglobin, C‐peptide, and lipids comparing 1‐year follow‐up levels to end of treatment (week 16) and baseline (week 0) levels. Results: From end of treatment to the 1‐year follow‐up, body weight had increased in the liraglutide‐treated group. However, compared to baseline levels, the placebo‐subtracted body weight loss remained significantly reduced (−3.8 kg, 95% CI: −7.3 to −0.2, P  =   0.04). Fasting glucose, glycated hemoglobin, C‐peptide, and lipids had each returned to baseline levels 1 year after stopping liraglutide. Conclusion: The body weight reduction during 16 weeks of liraglutide treatment was partially sustained 1 year after the intervention was completed. However, the improvements in other metabolic parameters returned to baseline levels.